Matthew - Reeves, Rodney (The story of God Bible commentary, 2017)
A new commentary for today's world, The Story of God Bible Commentary explains and illuminates each passage of Scripture in light of the Bible's grand story. The first commentary series to do so, SGBC offers a clear and compelling exposition of biblical texts, guiding everyday readers in how to creatively and faithfully live out the Bible in their own contexts. Its story-centric approach is ideal for pastors, students, Sunday school teachers, and laypeople alike. Three easy-to-use sections designed to help readers live out God's story